Lichenoid lesion on the tongue in a patient with Laugier-Hunziker Syndrome - Oliveira, Fabiana da Silva de; Trench, Marcela Adell; Lemos , Celso Augusto; Sugaya, Norberto Nobuo (Journal of Oral Diagnosis, 2025)
A 75-year-old woman presented with a painful lesion on the right lateral border of the tongue, seeking diagnosis and treatment. Clinical examination revealed erosions with whitish striae, consistent with a lichenoid lesion, which was confirmed by histopathology. The lesion was managed symptomatically with low-level laser therapy and monitored over time. In addition, the patient exhibited pigmented macules on the lips and longitudinal melanonychia. After ruling out other local and systemic conditions, a diagnosis of Laugier-Hunziker syndrome (LHS) was established. Laugier-Hunziker syndrome (LHS) is a rare, benign pigmentary disorder characterized by slate-gray to dark brown macules on the mucosa, nails, and acral sites. It predominantly affects individuals of French and Italian descent, but it has also been observed in Hispanics, Arabs, and Asians. To date, approximately 200 cases of LHS have been described in the literature, with no documented association with oral lichenoid lesions. This report illustrates the concomitant occurrence of these two conditions, an association not yet recognized in the literature, which should be considered anecdotal so far. This report highlights the importance of thorough clinical evaluation and awareness of rare conditions, such as LHS, to prevent misdiagnoses and enhance understanding of its potential associated manifestations.